Anglicanism - Neill, Stephen, 1900-1984. ([Harmondsworth, Middlesex] Penguin Books, 1958)
"Everyone knows that the British Empire has grown into the Commonwealth of independent nations, ten of which are in their own right members of the United Nations. Not everyone is aware that by a similar process the familiar 'C. of E.' has grown into the Anglican Communion, in which are to be found no less than fourteen fully independent and self-governing Churches. When Anglican chaplains to the Forces arrived in India during the war, some of them were startled to find that the licence issued to them by the Archbishop of Canterbury was without effect in India, and that they could not perform any spiritual act on Indian soil unless they had a licence to do so from the bishops of the Church of India, Burma, and Ceylon. How has all this come about? What is the Anglian Communion? How has it come into being? How does it work today? What holds it together, in its peculiar combination of independence and mutual loyalty? What is the status and significance of the Lambeth Conference? What is the relationship between the Anglican Communion and other Christian bodies? What part is it playing in the ecumenical movement and in the movement for Christian union today?Such are some of the questions to which this book attempts, in the light of history and theology, to provide straightforward and non-technical answers." - Publisher
Includes bibliographical references
Keywords: Anglican Communion; History